Perencanaan Strategis SI/TI Menggunakan Metode Ward and Peppard di PT. Niasa - Yusman, Nova Indrayana; Furqon, Muhamad; Wiryawan, Muhammad Ryzki (Ma'soem University, 2024)
PT. Niasa is a company operating in the processed food industry. In conducting its business, PT. Niasa does not plan the use and use of SI/IT well, so it does not focus on supporting the company's business strategy. There is a strong need for business strategy (SI/TI) to support the operational business of the company. Strategic planning of information systems is one of the keys to achieving corporate goals, and the strategic planning model discussed in this study adopts the approach of Ward and Peppard. Ward's and Peppar's methods are models for developing strategic plans for information systems for companies in the industry. Some of the analytical methods used are value chain analysis, SWOT analysis, and McFarlan Strategic Grid.